Histological and histochemical assessment of short-term events in peri-implant bone for osteoinductivity evaluation of functional-protective implant coatings - Loskutov, O.Ye.; Shponka, I.S.; Bondarenko, O.O.; Bondarenko, N.S.; Bozhko, A.G. (Medicni Perspektivi, 2021)
Utilization of functional-protective coatings for implants based on corundum ceramics seems promising from the point of view of stability, bioinertness, and low cost. In order to study the histological criteria for evaluating the osteoinductive properties of functional protective coatings, 6 types of coatings were studied on an experimental animal model: 90 Wistar rats were implanted with 6 test types of implants with various combinations of surface treatment (sand-blasting, surface treatment with a plasma torch with simultaneous application of aluminum oxide, powdered titanium, etc.) with an exposure of 1, 2 and 4 weeks. After euthanasia, a histological examination of decalcified bone with Masson-Goldner trichrome staining and TRAP-histochemical reaction for osteoclasts was performed. The obtained results demonstrated significantly higher osteoinductive properties of functional protective coatings with a more pronounced roughness (Ra>10 μm) compared to an untreated titanium surface after 2 (p<0.01) and 4 (p<0.05) weeks of implantation. The corundum ceramic coating prevented the formation of implant wear particles, hence contributed to the stabilization of the newly formed bone. Therefore, the use of functional protective implant coatings based on corundum ceramics can increase the survival rate of conventional titanium implants, since the combination of factors such as surface roughness, mechanical stability, and chemical inertness of coatings with corundum ceramics provides better osteoinductive properties of implant materials.